Offset or reduce: How should firms implement carbon footprint reduction initiatives? - Nils Roemer; Gilvan C. Souza; Christian Tröster; Guido Voigt (Production and Operations Management, 2023)
Carbon emissions reduction initiatives have received considerable attention at the corporate level. Companies such as Daimler, Apple, and Amazon have publicly declared their goal of becoming carbon neutral or “net zero” in a near future. They are responding to a growing demand for sustainable products and services. Companies have a variety of options for carbon emission reductions available to them, including internal reductions such as adopting renewable energy as well as buying carbon offsets. This raises the question of whether consumers perceive the different types of carbon emission reductions as equivalent, or whether they favor the implementation of internal measures. We investigate this issue empirically through surveys and incentive-compatible discrete choice experiments. We find clear consumer preferences and willingness to pay for companies to reduce their carbon footprint when companies internally reduce their controllable emissions rather than buying carbon offsets for these emissions, and it is especially true for eco-conscious consumers. Consumers place roughly the same value, however, on internal reductions in controllable emissions and buying offsets for the same amount of uncontrollable~emissions.
Keywords: 650; behavioral operations; carbon footprint; carbon offsets; sustainable operations